Tannerella forsythia‐produced methylglyoxal causes accumulation of advanced glycation endproducts to trigger cytokine secretion in human monocytes. (2nd May 2018) - Settem, R.P.; Honma, K.; Shankar, M.; Li, M.; LaMonte, M.; Xu, D.; Genco, R.J.; Browne, R.W.; Sharma, A.
Abstract : The periodontal pathogen Tannerella forsythia has the unique ability to produce methylglyoxal (MGO), an electrophilic compound which can covalently modify amino acid side chains and generate inflammatory adducts known as advanced glycation endproducts (AGEs). In periodontitis, concentrations of MGO in gingival‐crevicular fluid are increased and are correlated with the T. forsythia load. However, the source of MGO and the extent to which MGO may contribute to periodontal inflammation has not been fully explored. In this study we identified a functional homolog of the enzyme methylglyoxal synthase (MgsA) involved in the production of MGO in T. forsythia . While wild‐type T.forsythia produced a significant amount of MGO in the medium, a mutant lacking this homolog produced little to no MGO. Furthermore, compared with the spent medium of the T. forsythia parental strain, the spent medium of the T. forsythia mgsA ‐deletion strain induced significantly lower nuclear factor‐kappa B activity as well as proinflammogenic and pro‐osteoclastogenic cytokines from THP‐1 monocytes. The ability of T. forsythia to induce protein glycation endproducts via MGO was confirmed by an electrophoresis‐based collagen chain mobility shift assay. Together these data demonstrated that T. forsythia produces MGO, which may contribute to inflammation via the generation of AGEs and thus act as a potential virulence factor of the bacterium.